Estimating “Mean-State” July (1985–2007) N2O Fluxes in the Northern Gulf of Mexico Hypoxic Region: Variation, Distribution, and Implication - Kim, Il-Nam (Frontiers in Marine Science, 2018)
Along the Texas-Louisiana continental shelf in the northern Gulf of Mexico (nGOM) is a region frequently referred to as the “Dead Zone” due to severe oxygen depletion caused by eutrophication. Owing to its characteristics, it is expected to be an oceanic source region for nitrous oxide (N2O) emissions to the atmosphere during the hypoxic events. However, there is little known about whether the nGOM is source or sink region for atmospheric N2O. Here, we estimate “mean-state” July (1988‒2007) N2O fluxes from the nGOM, using simple modeling approach. The estimated mean N2O fluxes for July across the air-sea interface ranged from +0.9±11.7 to +14.3±15.0 μmol N2O m-2 d-1 with a mean value of +6.1±9.0 μmol N2O m-2 d-1 (+: sea → air). Our estimates were in reasonable agreement with the few available summer measurements, and suggested that the nGOM hypoxic region acts as a source of atmospheric N2O during the month of July between 1985 and 2007. Local regions influenced by the Mississippi and Atchafalaya Rivers showed higher N2O fluxes to the atmosphere than other regions. If the area affected by nutrient loading and the resulting hypoxia expands, the nGOM may become an even stronger oceanic N2O “hot spot” source region. Therefore, future study, based on in-situ observations, is necessary to elucidate N2O dynamics in the nGOM hypoxic region.